If it's not what You are looking for type in the equation solver your own equation and let us solve it.
5x-4=3x+24+9x
We move all terms to the left:
5x-4-(3x+24+9x)=0
We add all the numbers together, and all the variables
5x-(12x+24)-4=0
We get rid of parentheses
5x-12x-24-4=0
We add all the numbers together, and all the variables
-7x-28=0
We move all terms containing x to the left, all other terms to the right
-7x=28
x=28/-7
x=-4
| 5(4x+8)=48 | | 9=16x-7 | | 4x+23=7x+2 | | 3x+12=42+2x | | 982=b+51 | | 3x+32=7(8-3x) | | 4x+26+5x=180 | | -4(-8-8v)-1=-2-v | | q7+8=19 | | 2n+12=45 | | 3/7+b/3=7/12 | | a-17=0 | | 5(d+1)=5 | | -8.7+x/1.1=7 | | x/7=x/14 | | 3x+47=-95+5x | | 25w-w=-35w-25 | | 12x^2+12×-9=0 | | 3u=20(-2u) | | (14x-47)+(8x-15)=180 | | (3+√8)^x+(3-√8)^x=34 | | -8-19=x | | 5x-6+3+7x=-8+1-3x | | 3(y/2-6)=12 | | r6=9 | | u=42/6 | | 2v+5-8v=-14 | | 9x–4=8x+4 | | 6x-7x+3-9x=3+5+4x | | X=03y=20 | | c-21=46 | | 3(3g+2)=3(4g-1 |